Performance Audit in The Vision of Public Sector Management. The Case of Romania - Aurelia Stefanescu; Cristina-Petrina Trincu-Drăgusin (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: What is the impact of the performance audit missions on the activity of the Romanian public institutions? Motivation - Public resources' management and use, public sector entities' performance, in the context of the economic environment turbulences and of the complexity and heterogeneity of the public services demand are of interest to a wide range of interested parties. Thus, the informational valences of the performance audit represent for the public sector management, a credible and relevant information source to substantiate the decision-making process focused on performance and circumscribed to the community members. Idea - The paper includes an empirical research on the investigation of the public sector management perception regarding the impact of the performance audit missions performed by the Romanian Court of Accounts, on the public institutions activity. Data - Information regarding the performed missions and the entities subject to performance audit was collected by reviewing the Romanian Court of Accounts' portfolio of publications (available online on the institution's official website). The email addresses of the respondents were collected by consulting the official web pages of the audited entities (contact section). Tools - The research is based on the study of the public sector management's perception regarding the performance audit missions performed by the Romanian Court of Accounts. In this regard, we developed and disseminated questionnaires to the management of public sector entities subject to performance audit within the period 2015-2019. Complementarily, in order to identify the tendencies and the respondents' homogeneous perceptions, the descriptive analysis is completed by cluster analysis and multidimensional scaling. Data processing, clustering and the results' analysis were performed using the SPSS statistical software. Findings - The research results show that performance auditing contributes to improving the economicity, efficiency and effectiveness in the public resources use, but its usefulness is inversely proportional to the professional experience of the respondents within the audited entity. The respondents also consider that the performance audits' objectives are appropriate to the sensitive areas related to the activity of public institutions, and their results provide a fair image regarding the public resources' management and use. Concerning the performance audit reports, the respondents consider them objective, rigorous, credible, and the collaboration and communication of the auditors with the entity are appreciated as successful elements of the performance audit missions. Contribution - The paper adds value to the specialized literature, given that the performance audit issue in the vision of the public sector management has not been addressed in Romania, being also limited internationally. The research results are also of interest to both the professional and the socio-economic environment, concerned with the public sector entities performance.
Keywords: M42; C38; H83; 650; performance audit; public sector; interested parties; supreme audit institution; Romania; Court of Accounts